Surface characterization of lithium disilicate ceramic after nonthermal plasma treatment - Vechiato Filho, Aljomar Jose [UNESP]; Santos, Daniela Micheline dos [UNESP]; Goiato, Marcelo Coelho [UNESP]; Medeiros, Rodrigo Antonio de [UNESP]; Moreno, Amalia [UNESP]; Bonatto, Liliane da Rocha [UNESP]; Rangel, Elidiane Cipriano [UNESP] (Elsevier B.V., 2014)
Statement of problem. Surface transformation with nonthermal plasma may be a suitable treatment for dental ceramics, because it does not affect the physical properties of the ceramic material.Purpose. The purpose of this study was to characterize the chemical composition of lithium disilicate ceramic and evaluate the surface of this material after nonthermal plasma treatment.Material and methods. A total of 21 specimens of lithium disilicate (10 mm in diameter and 3 mm thick) were fabricated and randomly divided into 3 groups (n=7) according to surface treatment. The control group was not subjected to any treatment except surface polishing with abrasive paper. In the hydrofluoric acid group, the specimens were subjected to hydrofluoric acid gel before silane application. Specimens in the nonthermal plasma group were subjected to the nonthermal plasma treatment. The contact angle was measured to calculate surface energy. In addition, superficial roughness was measured and was examined with scanning electron microscopy, and the chemical composition was characterized with energy-dispersive spectroscopy analysis. The results were analyzed with ANOVA and the Tukey honestly significant difference test (alpha=.05).Results. The water contact angle was decreased to 0 degrees after nonthermal plasma treatment. No significant difference in surface roughness was observed between the control and nonthermal plasma groups. Scanning electron microscopy and energy-dispersive spectroscopy images indicated higher amounts of oxygen (O) and silicon (Si) and a considerable reduction in carbon (C) in the specimens after nonthermal plasma treatment.Conclusions. Nonthermal plasma treatment can transform the characteristics of a ceramic surface without affecting its surface roughness. A reduction in C levels and an increase in 0 and Si levels were observed with the energy-dispersive spectroscopy analysis, indicating that the deposition of the thin silica film was efficient.